2012
DOI: 10.1515/bot-2011-0064
|View full text |Cite
|
Sign up to set email alerts
|

Variation in rhodolith morphology and biogenic potential of newly discovered rhodolith beds in Newfoundland and Labrador (Canada)

Abstract: For the first time the subarctic northwestern Atlantic, we examined variation in rhodolith (Lithothamnion glaciale) morphology and biogenic potential in two large (>500 m2) rhodolith beds we discovered recently between the depths of 5–25 m off St. Philip’s and Holyrood, Newfoundland and Labrador. Rhodoliths at St. Philip’s were >50% larger and contained 7% more internal space in deep (15–17 m) than shallow (8–10 m) water, whereas shallow rhodoliths were >180% larger at Holyrood than at St. Philip’s. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
58
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 81 publications
9
58
1
Order By: Relevance
“…Algarve). The lack of an obvious pattern in our results could be attributed to the fact that our study combines data from a wide range of rhodolith beds while previous studies often focused on changes within a single or a few beds (Bosellini & Ginsburg 1971, Bosence 1976, Peña & Bárbara 2008, Basso et al 2009, Rosas-Alquicira et al 2009, Gagnon et al 2012, Teichert et al 2012. Nonetheless, further studies including measurements of wave energy and tidal currents at the study sites will be required to assess the actual influence of hydrodynamic energy on rhodolith shape.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Algarve). The lack of an obvious pattern in our results could be attributed to the fact that our study combines data from a wide range of rhodolith beds while previous studies often focused on changes within a single or a few beds (Bosellini & Ginsburg 1971, Bosence 1976, Peña & Bárbara 2008, Basso et al 2009, Rosas-Alquicira et al 2009, Gagnon et al 2012, Teichert et al 2012. Nonetheless, further studies including measurements of wave energy and tidal currents at the study sites will be required to assess the actual influence of hydrodynamic energy on rhodolith shape.…”
Section: Discussionmentioning
confidence: 77%
“…On the other hand, we observed that largest maerl was linked to deep sites in Brittany (Trevignon, P. calcareum and L. corallioides) and S Portugal (Algarve2, Phymatolithon sp.3). Other authors have reported cases where rhodolith size either increases (Amado-Filho et al 2007, Gagnon et al 2012 or decreases (Steller & Foster 1995, Bahía et al 2010 with depth. However, in our study, the relationship between size and depth is far from clear because other deep sites (San Francisco, Ons) did not follow the pattern and contained small rhodoliths.…”
Section: Discussionmentioning
confidence: 98%
“…Adey (1966) described several beds along the coast of Newfoundland and Labrador, and other investigated the primary species of coralline algae and their distribution (Adey & Adey 1973, Adey et al 2005, Adey & Hayek 2011. Gagnon et al (2012) carried out the first quantitative research about rhodolith bed structure and associated fauna. They compared rhodolith shape and dominant macro-and crypto-faunal species in two beds in Conception Bay, Newfoundland, and found that two species (the daisy brittle star Ophiopholus aculeata and the mottled red chiton Tonicella marmorea) represented over 82% of total invertebrates in both beds.…”
Section: Figure 28mentioning
confidence: 99%
“…were commonly observed displacing at the surface of the rhodolith bed (Gagnon et al 2012). Conception Bay experiences semi-diurnal tidal periods and is exposed to strong winter storms that frequently come from the north in the late Fall (Brodie et al 1993).…”
Section: Figure 28mentioning
confidence: 99%
“…In the literature growth-form variations have been attributed to differences in environmental factors such as hydrodynamic conditions, depth, coastal morphology or bioturbation (Bosellini and Ginsburg 1971, RiosmenaRodríguez et al 1999, Goldberg 2006, Gagnon et al 2012, However, recent studies have shown that the ability to form rhodoliths may be caused by a genetic feature, a plesiomorphic trait inherited from a common ancestor (Hernández-Kantún unpublished data). Further genetic and environmental studies on rhodolith-forming species are obviously necessary if we are to accurately understand the factors generating their development.…”
Section: Growth-form Differences In Populationsmentioning
confidence: 99%